Statistika Menyapa Sekolah: Inspirasi, Edukasi, dan Aplikasi Nyata dalam Meningkatkan Literasi Statistika dan Visualisasi Informasi di SMA Islam Al Mujaddid Kota Sabang - Marzuki, Marzuki; Ula, Akramul; Lulhaq, M Imam Bagus; Munandar, Jefri; Aprilian, Hikmal; Alfiandi, Alfiandi; Hifdhillah, T Afrah; Saputra, Deni (PELITA NUSA TENGGARA, 2025)
Community service is an essential component of the Tri Dharma of Higher Education, aimed at making a tangible contribution to society. This activity sought to enhance statistical literacy and information visualization skills among students of SMA Islam Al Mujaddid Kota Sabang through campus education and infographics training. The activity was carried out on April 19, 2025 , and was attended by 32 participants. The implementation method involved a participatory approach through interactive counseling and hands-on training. The results of the activity indicated an improvement in students’ understanding of statistics, as well as strong interest and skills in creating infographics and conveying information visually. This program successfully strengthened the synergy between higher education institutions and secondary schools. It also produced tangible outputs, including a basic training module and student-designed infographics. The activity opens up opportunities for further and continuous training initiatives.